2017
DOI: 10.1002/anie.201709875
|View full text |Cite
|
Sign up to set email alerts
|

Triple Bonds Between Iron and Heavier Group 15 Elements in AFe(CO)3 (A=As, Sb, Bi) Complexes

Abstract: Heteronuclear transition-metal-main-group-element carbonyl complexes of AsFe(CO) , SbFe(CO) , and BiFe(CO) were produced by a laser vaporization supersonic ion source in the gas phase, and were studied by mass-selected IR photodissociation spectroscopy and advanced quantum chemistry methods. These complexes have C structures with all of the carbonyl ligands bonded on the iron center, and feature covalent triple bonds between bare Group 15 elements and Fe(CO) . Chemical bonding analyses on the whole series of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…There are well‐characterized complexes with nitride ligands [22, 23, 25–27] . Fe‐X triple bonds also exist with carbyne ligands [28] and mass‐spectrometry has suggested existence of triple bonds with heavier group 14 and 15 elements, [29, 30] or even the existence of the Fe‐B quadruple bond [31] . However, these bonds have not been characterized by means of vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…There are well‐characterized complexes with nitride ligands [22, 23, 25–27] . Fe‐X triple bonds also exist with carbyne ligands [28] and mass‐spectrometry has suggested existence of triple bonds with heavier group 14 and 15 elements, [29, 30] or even the existence of the Fe‐B quadruple bond [31] . However, these bonds have not been characterized by means of vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations presented are in contrast to those recently reported by Wang et al on [EFe(CO) 3 ] -(E = N-Bi), who found E − − − Fe triple bonds in all cases. 14 They performed single-point CASSCF calculations whose wavefunctions were predominantly composed of a single configuration (c. 90% for E = As-Bi), in support of their closed-shell DFT calculations. This serves to highlight the impact of the many actinide valence orbitals in influencing their chemistry.…”
mentioning
confidence: 90%
“…The AO contributions are listed in Table S5. The singly occupied 11a 1 MO, with composition of 78.4 % Be (31.5 % 2s + 46.9 % 2p) and 13.3 % Fe, is more or less non‐bonding, because it is antibonding between Be 2s and Fe 3d orbitals while being bonding between Be 2p and Fe 3d orbitals based on the three‐orbital interaction model [10d] . The doubly degenerate 9e 1 MOs involving Fe d xy and dx2-y2 orbitals are innocent for Be−Fe bonding.…”
Section: Figurementioning
confidence: 99%